Sleep in Women: A Review. (February 2015) - Bei, Bei; Coo, Soledad; Baker, Fiona C; Trinder, John
<x xml:space="preserve">Abstract</x> Sleep complaints are common in women, and women are more likely to suffer from insomnia than men. Multiple factors across a woman's lifespan, including hormonal changes, age‐related physiological changes, psychosocial factors, the presence of sleep disorders, and physical and mental health conditions, can contribute to complaints of poor sleep in women. This article reviews the literature on the characteristics of, and contributing factors to, subjectively and objectively measured sleep during the menstrual cycle, pregnancy, and post‐partum period, as well as the menopausal transition and postmenopause. Evidence from both subjective and objective measurements supports the presence of chronic sleep fragmentation associated with pregnancy, acute sleep deprivation during labour and the immediate post‐partum periods, as well as disrupted sleep during the first few months after childbirth. While there is evidence for menstrual cycle and menopause related sleep disturbance based on women's self report, findings from objectively measured sleep have been mixed. Observational and intervention studies on the relationship between sleep and women's psychological well‐being suggest that underlying causes of sleep disturbance across a woman's lifespan are often multi‐factorial. Comprehensive assessments and targeted interventions are needed in managing sleep problems in women. Cognitive behavioural interventions have been shown to reduce sleep complaints during the perinatal and menopausal periods, and improvements in sleep are likely to lead to improvements in women's overall well‐being.